Effect of Cottonseed Extracts on Haematological Parameters of Albino Male Mice - Inaam Noori Ali; Sabah A.R. Al-Obaidi; Muhammad Baqir M-R. Fakhrildin (College of Pharmacy / Mustansiriyah University, 2010)
The objectives of the present study are to determine the effect of different concentrations of aqueous and oil extracts of cottonseed on haematological parameters. Groups of male mice were orally administered aqueous extract [20mg/kg/l day (G2) and 40 mg/kg/day (G3)] and other groups were administered oil extract [20% (G5) and 40% (G6)] for six weeks. The results showed that there was a significant (P<0.05) reduction in Hb values for mice treated with 20% and 40% oil extract as compared to the control. Also, significant (P<0.05) reduction in the percentage of PCV were noticed for both concentrations of extracts as compared to the control groups. While non significant (P>0.05) differences were shown in RBC and WBC count among G5and G6 as compared to G4. Significant (P<0.05) increment in the platelet count was shown in G2, G3, G5 and G6 as compared to the control. Differential leukocyte analysis showed that a significant (P<0.05) reduction was observed in the percentage of lymphocyte and significantly (P<0.05) increase neutrophils in G2 and G3 as compared with G1 and in G6 as compared to G4. While, monocytes (%) were significantly (P<0.05) decrease in G5 and G6 as compared to G4. However, 40mg/kg/day aqueous extract dose demonstrated a significant (P<0.05) increment in the percentage of eosinophil and basophile cells as compared to G1.